2016
DOI: 10.1080/1028415x.2016.1180859
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of brain-derived neurotrophic factor (BDNF) gene expression in hypothalamus of obese rats: Modulation by omega-3 fatty acids

Abstract: Obesity causes down-regulation of BDNF gene expression that can be reversed by ω-3 FAs treatment, making them an interesting treatment approach for obesity and metabolic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Exenatide treatment positively affects BDNF signaling in 3xTg-AD CD mice and prevents the development of neurotrophic signaling impairment in 3xTg-AD HFD animals HFD administration impairs BDNF neurotrophic signaling along with the downstream activation of the cAMP response element-binding (CREB) protein, a transcription factor essential for synaptic plasticity and learning and memory processes 35,36 . Compared to 3xTg-AD CD animals, WB analysis performed on hippocampal, cortical, and cerebellar homogenates obtained from the study animals showed decreased BDNF levels in 3xTg-AD HFD mice (Fig.…”
Section: Aβ-and Tau-pathology In 3xtg-ad CD and 3xtg-ad Hfd Micementioning
confidence: 99%
“…Exenatide treatment positively affects BDNF signaling in 3xTg-AD CD mice and prevents the development of neurotrophic signaling impairment in 3xTg-AD HFD animals HFD administration impairs BDNF neurotrophic signaling along with the downstream activation of the cAMP response element-binding (CREB) protein, a transcription factor essential for synaptic plasticity and learning and memory processes 35,36 . Compared to 3xTg-AD CD animals, WB analysis performed on hippocampal, cortical, and cerebellar homogenates obtained from the study animals showed decreased BDNF levels in 3xTg-AD HFD mice (Fig.…”
Section: Aβ-and Tau-pathology In 3xtg-ad CD and 3xtg-ad Hfd Micementioning
confidence: 99%
“…The effect of n -3 PUFA in the brain alterations related to obesity was less studied, with hypothalamus being the major focus of the investigation. n -3 PUFA showed beneficial effects on modulating inflammation and hypothalamic function in rodents ( 23 , 26 , 33 ) and was able to reverse the negative effect on the brain-derived neurotrophic factor (BDNF) gene expression caused by obesity in the hypothalamus of rats ( 31 ) . A review of animal studies on n -3 PUFA for obesity (and related alterations) is summarised in Table 1.…”
Section: N-3 Pufa and Obesitymentioning
confidence: 99%
“…Essential fatty acids ω-3 can contribute to an increase in the proliferation and differentiation of hippocampal cells [52,53,55] which can reverse the decline of substances affecting neurogenesis process caused by aging [56]. DHA has a positive effect on the viability of neurons by inducing the formation of the neurotrophic factor BDNF [57] and own metabolic changes, in which it is metabolized to derivatives having neuroprotective activity -N-docosahexaenoylethanolamid (DEA) [58] and neuroprotectin D1 (NPD1) [59,60] .…”
Section: The Role Of Efas In the Functioning Of Cnsmentioning
confidence: 99%
“…NNKT ω-3 mogą wpływać na wzrost proliferacji i różnicowania komórek hipokampa [52,53,55] oraz odwracać spowodowany wiekiem spadek substancji oddziałujących na proces neurogenezy [56]. DHA wywiera korzystny efekt na żywotność neuronów poprzez indukcję powstawania czynnika neurotroficznego BDNF [57] oraz przemiany własne, w których metabolizowany jest do pochodnych o neuroprotekcyjnym działaniu -N-docosahexaenoylethanolamid (DEA) [58] oraz neuroprotektyny 1 (NPD1) [59,60].…”
Section: Rola Nnkt W Funkcjonowaniu Oununclassified